2022
DOI: 10.1186/s12905-022-01812-z
|View full text |Cite
|
Sign up to set email alerts
|

“Even if I’m undetectable, I just feel like I would die”: a qualitative study to understand the psychological and socioeconomic impacts of the COVID-19 pandemic on women living with HIV (WLWH) in Chicago, IL

Abstract: Background The COVID-19 pandemic has affected the health and well-being of people worldwide, yet few studies have qualitatively examined its cumulative effects on ciswomen living with HIV (WLWH). We aimed to explore how the pandemic has impacted WLWH, including challenges related to HIV care, employment, finances, and childcare. We also investigated how HIV status and different psychosocial stressors affected their mental health. Methods We perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
2
6
0
Order By: Relevance
“…While increased structural barriers to accessing treatment (e.g., longer wait times) negatively impacted participant perceptions of care, reduced privacy during care interactions was described as the primary challenge negatively affecting the quality and breadth of clinical consultation. Broadly, findings align with those of qualitative studies conducted in other settings, which have identified both new and increased barriers for PWH during the pandemic 1417,19,20 and differ from prior qualitative work in South Africa, which was conducted within a program for highly adherent PWH. 13
Figure 1.Conceptual map of themes.
…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…While increased structural barriers to accessing treatment (e.g., longer wait times) negatively impacted participant perceptions of care, reduced privacy during care interactions was described as the primary challenge negatively affecting the quality and breadth of clinical consultation. Broadly, findings align with those of qualitative studies conducted in other settings, which have identified both new and increased barriers for PWH during the pandemic 1417,19,20 and differ from prior qualitative work in South Africa, which was conducted within a program for highly adherent PWH. 13
Figure 1.Conceptual map of themes.
…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, PWH have described numerous pandemic-related challenges with their HIV care in other settings, including Ghana, Hong Kong, Pakistan, Uganda, the United States, and the United Kingdom. [14][15][16][17][18][19][20] These include increased personal challenges, such as increased economic struggle and mental health symptoms, and increased systems barriers, such as structural barriers to accessing services (e.g., cancellations) and reduced privacy.…”
Section: Introductionmentioning
confidence: 99%
“…8,27 These findings also counter previous studies reporting disproportionate mental health impact on PLWH. [4][5][6][7][8][9][10] Although our findings may be influenced by the demographics of our cohort (predominantly male, educated, economically stable and white), it is important that future work clarifies the psychological impact of pandemics on PLWH, as it will inform future pandemic policy and support. Our findings found that, despite a small sample size, a higher proportion of women, POC and those self-reporting economic instability reported dysfunctional pandemicrelated anxiety.…”
Section: Discussionmentioning
confidence: 98%
“…The detrimental impact on the mental health of PLWH during the pandemic has been reported in multiple settings. [3][4][5][6][7][8][9][10] There are many potential drivers of this. From a health perspective, PLWH have voiced concerns about being at greater risk of serious illness and death from COVID-19, 4,11 worry about access to healthcare services 12,13 and a heightened fear of HIV-status disclosure during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported that emotional distress caused by the pandemic affected adherence and retention, especially among newly diagnosed PLWH. [28][29][30] Long-term survivors, or individuals who have lived with HIV for several years, are at higher risk of multiple comorbidities 31,32 , more severe premature aging and cognitive dysfunction when living with HIV for longer than 10 yearsindependent of age in years. 27 Among those living with HIV for longer than 10 years, higher levels of HIV stigma, and social isolation 31,32 were reported, as well.…”
Section: Introductionmentioning
confidence: 99%